Case Report: 18F-PSMA PET/CT Scan in Castration Resistant Prostate Cancer With Aggressive Neuroendocrine Differentiation - Bergamini, Marco; Dalla Volta, Alberto; Caramella, Irene; Bercich, Luisa; Fisogni, Simona; Bertoli, Mattia; Valcamonico, Francesca; Grisanti, Salvatore; Poliani, Pietro Luigi; Bertagna, Francesco; Berruti, Alfredo (Frontiers in Oncology, 2022)
The development of a neuroendocrine phenotype as a mechanism of resistance to hormonal treatment is observed in up to 20% of advanced prostate cancer patients. High grade neuroendocrine prostate cancer (NEPC) is associated to poor prognosis and the therapeutic armamentarium is restricted to platinum-based chemotherapy. Prostate-specific membrane antigen (PSMA)-based positron emission tomography (PET)/computed tomography (CT) imaging has recently emerged as a potential new standard for the staging of prostate cancer and PSMA-based radioligand therapy (RLT) as a therapeutic option in advanced metastatic castration resistant prostate cancer (mCRPC). PSMA-based theranostic is not currently applied in the staging and treatment of NEPC since PSMA expression on neuroendocrine differentiated cells was shown to be lost. In this case series, we present 3 consecutive mCRPC patients with histologically proven high grade neuroendocrine differentiation who underwent PSMA-PET/CT and surprisingly showed high tracer uptake. This observation stimulates further research on the use of PSMA-based theranostic in the management of NEPC.